Environmental concerns in the development projects on rice farming under decentralized planning - Smitha K P (Department of Agricultural Extension, College of Agriculture, 2011)
The study entitled ‘Environmental concerns in the development projects on rice farming under decentralized planning’ was undertaken with the major objective of studying the nature and extent of environmental concerns in planning and implementation of development projects on rice farming under decentralized planning in Palakkad District. Environmental awareness and constraints perceived by stakeholders in planning and implementation of the projects were also studied. The research project was undertaken in Palakkad district, as the district accounts for about 1/3rd of the total area under rice cultivation of Kerala state. Four blocks, viz. Kollengode, Kuzhalmannam, Chittur and Alathur were selected purposively based on the highest area under rice. Thekkinchira, Nelliancaud, Manchira and Kolapadam padashekarams were randomly selected from the above four respective blocks. Ten each of beneficiary farmers, agricultural labourers, people’s representatives/social activists in the same padashekaram were selected randomly for the study. Thus a total of 40 beneficiary farmers, 40 agricultural labourers and 40 people’s representatives/social activists were selected from the study area. In addition to those included in the selected projects / padashekarams, extension functionaries from other regions of the district were also randomly selected, so as to make a sample size of 40. Thus a total of 160 respondents belonging to the four categories constituted the sample of this study. The data collected were statistically analyzed using arithmetic mean, percentage, canonical correlation analysis and principal component analysis. The study on environmental concerns and awareness of stakeholders revealed that the farmer respondents had high to medium level of environmental concerns and awareness. Most of the agricultural labourers possessed medium level of environmental concerns while all of them were in the medium awareness category. All the extension personnel and majority of people’s representatives/social activists had high awareness and concern for environment. In the nature of environmental concerns it was found that in the land and soil management dimension, most of the padashekarasamithi considered three technologies while planning viz. (1) practicing crop rotation with pulses/leguminous green manures /fringe cropping with cowpea (2) application of nitrogen and potassium in two to three split doses and (3) application of lime while all the farmer respondents adopted two technologies viz. (1) applying nitrogen and potassium in 2-3 split doses according to the duration of the variety and (2) incorporation of crop residue in the field. While majority of the samithis considered only a single water management technology in the planning stage (selection of suitable varieties based on water availability) all the respondents adopted three major water management practices viz.(1) summer ploughing, (2) land/leveling/ puddling and (3) maintaining standing water as per crop requirement. All the samithis included augmentation of parasite / predator population in the field / use of natural enemies like Pseudomonas in the planning stage. Majority of the farmers avoided poaching and killing of birds and animals in rice fields. Selection of right season was considered in the planning stage by all the samithis and all the respondent farmers ploughed the field and exposed it to sun as a part of the plant protection practices. With respect to the extent of environmental concerns in the planning stage, majority of the farmers were found to be in the lower class of adoption with regard to land and soil management, water management, biodiversity conservation and plant protection practices while most of them were in the medium category in the implementation stage of all the four dimensions. Percentage adoption of land and soil management practices, water management, biodiversity conservation and plant protection practices was very high over planning and it was the highest in case of water management dimension. The above results show the inefficient planning at padashekarasamithi level and a better adoption and environmental concerns at the farmer level. Analysis of the relationship between the dependent variables (environmental concerns, awareness and extent of environmental concerns reflected in adoption of eco-friendly technologies) and profile characteristics of farmers revealed that environmental concern is the most important dependant variable and the profile characteristics viz. perception on the importance of mitigating environmental degradation, indigenous wisdom orientation, knowledge on eco-friendly rice cultivation, experience in eco-friendly farming, sense of empowerment, risk orientation, export orientation, educational status and participation in environment related activities contributes the most in developing environmental concerns and awareness. In the case of all other respondents out of the two dependent variables viz. environmental concerns and awareness, environmental concern is the most important dependent variable than environmental awareness. The variables sense of empowerment, experience in eco-friendly farming, knowledge on eco-friendly rice cultivation, perception on the importance of mitigating environmental degradation, age and indigenous wisdom orientation play crucial role in developing concern and awareness on environment in agricultural labourers while communication effectiveness, decision making ability and participation in environmental activities have the highest influence on the dependent variables in the case of extension personnel. Perception on the importance of mitigating environmental degradation, educational status, indigenous wisdom orientation, leadership, attitude towards group management and participation in environmental activities play very important role in defining environmental concern and awareness of people’s representatives / social activists. The B-C ratio of eco-friendly rice cultivation, conventional rice cultivation and cow based minimum budget rice farming (Gō-adharitha krishi) was 1.39, 1.79 and 2.2 respectively. The major reason for this is the higher cost of cultivation incurred in the case of eco-friendly rice cultivation which is due to the high cost of organic inputs and its application. But the price in the market is the same irrespective of the methods of production, which reduce the profit for eco-friendly farmers. Cow based minimum budget rice farming (Gō-adharitha krishi) portrays the success of eco-friendly farming by way of value addition and better marketing. The mean social benefit-cost ratio for all the respondents was high, which substantiates the general perception that social benefits derived from eco-friendly rice farming was higher than the social costs. The dimensions such as non- remunerative price, higher cost of cultivation and inconvenience in handling eco-friendly inputs contributed higher magnitude of variation towards social cost and the dimensions, superior quality of rice, enrichment of biodiversity, improvement in water quality and self-development contributed to higher magnitude of variations towards social benefit. Most of the farmers considered padashekarasamithi as a supplier of inputs from krishi bhavans, which was a major constraint in the planning stage while in the implementation stage the major constraint perceived by them was the labour unavailability. The labourers professed labour unavailability, lack of knowledge on eco-friendly techniques, lack of good quality, certified organic inputs in the market and higher cost of these inputs as the major constraints in the implementation stage. The major constraints according to the extension personnel were lack of co-ordination among the members of padashekarasamithi in the planning stage and labour unavailability, lack of good quality, certified organic inputs in the market in the implementation stage. While in the case of people’s representatives/social activists the major constraint perceived in the planning stage was the farmers outlook of padashekarasamithi as a mere input supplier of krishi bhavan. This group of stakeholders felt labour unavailability and problems in marketing organic rice due to its difficulty in getting it certified as the major constraints in the implementation stage. Some of the important policy prescriptions in the light of the study which the government should undertake are (i) offer incentive price for rice produced in an eco-friendly way (ii) provide assured market and farmer-customer networking (iii) simplify procedures of organic certification (iv) develop certification procedures for eco-friendly rice (v) value addition and (vi) offer incentives for farmers practicing clean agriculture (vii) encourage and conscientize farmers for cultivation of traditional varieties and use of indigenous wisdom (viii) redefining and updating organic farming policy (ix) encourge group approach in organic rice farming (x) encourage mixed farming (xi) maintain biodiversity register for grama panchayats and (xii) ensure availability of eco-friendly inputs .